2014
DOI: 10.2196/jmir.3085
|View full text |Cite|
|
Sign up to set email alerts
|

The Psychometric Properties of CollaboRATE: A Fast and Frugal Patient-Reported Measure of the Shared Decision-Making Process

Abstract: BackgroundPatient-centered health care is a central component of current health policy agendas. Shared decision making (SDM) is considered to be the pinnacle of patient engagement and methods to promote this are becoming commonplace. However, the measurement of SDM continues to prove challenging. Reviews have highlighted the need for a patient-reported measure of SDM that is practical, valid, and reliable to assist implementation efforts. In consultation with patients, we developed CollaboRATE, a 3-item measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
275
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 270 publications
(280 citation statements)
references
References 38 publications
0
275
0
5
Order By: Relevance
“…Although these rates of engagement compare favorably with a number of other e-health interventions (62), there are notable examples of online interventions in cancer survivors that yield higher levels of involvement (63). For example, in an online health behavior change intervention, Surviving and Thriving with Cancer , Bantum et al (64) demonstrated very high levels of user participation, at least with respect to posting content. Because of differences in intervention content and procedures, in addition to differences in how engagement is measured across interventions, it is very difficult to evaluate which intervention elements are most critical for improving effect sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Although these rates of engagement compare favorably with a number of other e-health interventions (62), there are notable examples of online interventions in cancer survivors that yield higher levels of involvement (63). For example, in an online health behavior change intervention, Surviving and Thriving with Cancer , Bantum et al (64) demonstrated very high levels of user participation, at least with respect to posting content. Because of differences in intervention content and procedures, in addition to differences in how engagement is measured across interventions, it is very difficult to evaluate which intervention elements are most critical for improving effect sizes.…”
Section: Discussionmentioning
confidence: 99%
“…9 24 This scoring technique is a strategy for aiding interpretation while avoiding potential ceiling effects common among clinician performance assessments completed by patients. 9 Incomplete CollaboRATE surveys were not included in analysis.…”
Section: Methodsmentioning
confidence: 99%
“…CollaboRATE has demonstrated psychometric soundness, 9 and has also been used in a demonstration project to assess differences in SDM across 34 clinical teams in England. 10 In addition, Blue Shield of California is using CollaboRATE to assess SDM as part of a preauthorisation process for joint replacement.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Elwyn suggests questions along three constructs related to patient understanding: information provision, preference elicitation, and preference integration of their perspective into final treatment decisions 10 : The construct is measured via patient report of the amount of clinician effort to help a patient (1) understand the health issues, (2) listen to the things that matter most, and (3) include what matters most when choosing what to do next. 11,12 The measure has the potential advantage of low patient burden and high practical use in a variety of medical settings.…”
Section: Improving Measurement Of Sdmmentioning
confidence: 99%